2018
DOI: 10.1002/bmb.21197
|View full text |Cite
|
Sign up to set email alerts
|

Is learning outcome after team based learning influenced by gender and academic standing?

Abstract: Team based learning (TBL) is a time tested teaching-learning (T-L) tool involving collaborative learning but has hardly been tested for teaching clinical biochemistry to undergraduate medical students. The present study was designed to (a) compare problem solving skills of first year MBBS students after attending a TBL session on 'organ function test' with that of the students taught the same topic by didactic lecture, (b) assess their perception towards TBL and (c) evaluate if difference in academic standing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…Burgess, Ayton, and Mellis [ 11 ] showed that students’ GRAT scores were lower than their IRAT scores. Das et al [ 12 ] investigated if gender was a variable that can affect TBL outcomes. They concluded that female students exhibited better achievement in tests that assessing problem solving skills than male students after TBL sessions.…”
Section: Introductionmentioning
confidence: 99%
“…Burgess, Ayton, and Mellis [ 11 ] showed that students’ GRAT scores were lower than their IRAT scores. Das et al [ 12 ] investigated if gender was a variable that can affect TBL outcomes. They concluded that female students exhibited better achievement in tests that assessing problem solving skills than male students after TBL sessions.…”
Section: Introductionmentioning
confidence: 99%
“…39 According to the self-determination theory, intrinsic motivation has a higher impact on students' academic performances. 40 Although traditional TBL has been reported to have a relative boosting effect on motivation because it contains elements that stimulate positive emotions and motivation in students, 41 other studies have reported that students who consider traditional TBL become less interested after the first two to three sessions and they recommend that TBL should be more interactive. 4,10 In this study, the experimental group perceived modified TBL as significantly more intereststimulating compared to the traditional TBL.…”
Section: Discussionmentioning
confidence: 99%
“…More than 70% of students perceived that the TBL session was interesting, encouraging, motivating, stress-free, and effective in this study. However, less than 50% of students perceived that TBL should replace all lecture sessions [16].…”
Section: Vázquezmentioning
confidence: 99%